An American Identity: The Shifting Sands of Democracy. Issue 1 (31st December 2022) - Nayar-Akhtar, Monisha
ABSTRACT: The bombings of the World Trade Twin Towers, New York, on September 11th, 2001, marked a turning point in American history. This paper explicates on the impact that this terrorist act on American soil had on an emerging nascent and complex multicultural identity. Informed by both my personal and professional life, the analytic work with Marianna, a young adult, sheds some light on internal and external factors that contribute to a feeling of safety in a world that feels increasingly unsafe.